POLA DAKWAH NAHDLATUL ULAMA DI KOTA BANJARMASIN - Fahmi, Fahmi (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Nahdlatul Ulama (NU) is a big organization in Indonesia and it spreads to the entire areas in Indonesia from  Aceh to Papua. In central area of Indonesia, precisely in Banjarmasin, NU can exists and recruits a lot of followers who are generally Pesantren-graduates,  which are called   "Nahdliyyin".  This paper  employed a  science of  da'wah  approach with a  focus on  "NU's  pattern of  da'wah  in  Banjarmasin", which includes verbal,  action,  and written models of preaching  (da'wah  bil lisan,  bil hal wa bil kitab).  This showed that  NU  tends to use verbal  and action model of  da'wah  rather than the written one,  such as magazine,  newspaper,  and so on.  This differs from other Islamic organizations such as Muhammadiyah and Al-Irsyad in Banjarmasin. However, the contribution of NU in developing and spreading  da'wah and NU's mission is significant despite the fact that it is carried out personally and not on behalf of the organization to which the community can look and recognize it as NU's Islamic preaching.